2022
DOI: 10.1007/s00520-022-07238-5
|View full text |Cite
|
Sign up to set email alerts
|

The intention to get COVID-19 vaccine and vaccine uptake among cancer patients: An extension of the theory of planned behaviour (TPB)

Abstract: The psychosocial impact of coronavirus disease 2019 (COVID-19) on human life is well-known. Although vaccine protection represents an effective way to control the spread of the virus, vaccination hesitancy may decrease individuals’ willingness to get vaccinated, including among cancer patients. Therefore, the objective of the current study was to examine the predictors of cancer patients’ intentions to receive COVID-19 vaccinations and vaccine uptake, using and integrating the theory of planned behaviour (TPB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“… 76 The EPPM constructs such as perceived efficacy, perceived fear and perceived severity, response efficacy, and perceived susceptibility were positively associated with COVID-19 preventive behaviors. 75 78 It was evidenced that 15% of the adult population in Nigeria had a high threat and efficacy domain 78 to practice preventive behavior, and among the adult population in Iran 54.6% of the participants were engaged in danger control and high-perceived efficacy. 77 This evidence explains the predictive ability of the EPPM on healthy preventive behavior.…”
Section: Discussionmentioning
confidence: 99%
“… 76 The EPPM constructs such as perceived efficacy, perceived fear and perceived severity, response efficacy, and perceived susceptibility were positively associated with COVID-19 preventive behaviors. 75 78 It was evidenced that 15% of the adult population in Nigeria had a high threat and efficacy domain 78 to practice preventive behavior, and among the adult population in Iran 54.6% of the participants were engaged in danger control and high-perceived efficacy. 77 This evidence explains the predictive ability of the EPPM on healthy preventive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, the need for mass vaccination to control COVID-19 infections comes at a time of growing skepticism about vaccinations and a reluctance or refusal to vaccinate, despite the availability of the vaccine, especially in developed countries (World Health Organization, 2020;Lunz Trujillo et al, 2021). Several studies have reported a high rate of COVID-19 vaccine hesitancy both in the general population (Sallam, 2021) and in high-risk groups, such as cancer patients (Mejri et al, 2022;Servidio et al, 2022). Consequently, vaccine skepticism threatens COVID-19 immunization efforts (Ball, 2020;Taylor et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This allowed a large cross-section of views to be analysed and correlated with clinical status across three predefined high-risk disease types. Our research enhances the understanding of the decision-making implications an underlying health condition may have when weighing the costs and benefits of accepting a vaccine in the context of a person’s disease or treatment, adding to information previously identified using fixed responses within surveys [ 17 , 18 , 24 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…Behavioural change is only expected if an individual perceives that the benefits outweigh risks. The HBM can be adapted to better understand, and thus specifically address, the multiple factors influencing an individual’s willingness or hesitancy to receive vaccines [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%